2023
DOI: 10.1021/acsnano.2c11503
|View full text |Cite
|
Sign up to set email alerts
|

Precision Modification of Monolayer Transition Metal Dichalcogenides via Environmental E-Beam Patterning

Abstract: Layered Transition Metal Dichalcogenides (TMDs) are an important class of materials that exhibit a wide variety of optoelectronic properties. The ability to spatially tailor their expansive property-space (e.g., conduction behavior, optical emission, surface interactions) is of special interest for applications including, but not limited to, sensing, bioelectronics, and spintronics/valleytronics. Current methods of property modulation focus on the modification of the basal surfaces and edge sites of the TMDs b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…nm (k, t) via Equation ( 5), followed by multiplying the off-diagonal element ρ (H) nm (k, t) by exp(− ∆t T 2 ), and finally transformed back to ρ (W) nm (k, t) via Equation (6). The above procedure is repeated until the end of the dynamics evolution.…”
Section: Theoretical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…nm (k, t) via Equation ( 5), followed by multiplying the off-diagonal element ρ (H) nm (k, t) by exp(− ∆t T 2 ), and finally transformed back to ρ (W) nm (k, t) via Equation (6). The above procedure is repeated until the end of the dynamics evolution.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…Furthermore, recent research has established that electrons in two-dimensional hexagonal materials possess an additional degree of freedom, known as the valley pseudospin, which corresponds to extreme points on the electron band dispersion curve. Such electrons are commonly found in materials such as graphene [4], layered transition metal dichalcogenides [5,6], and Weyl semimetal systems [7][8][9]. For instance, the energy band structure of graphene features two unequal yet degenerate Dirac points on the Fermi surface of the first Brillouin zone (BZ), referred to as the K 1 and K 2 valleys.…”
Section: Introductionmentioning
confidence: 99%
“…Bound quasiparticles (excitons and trions) are generally susceptible to factors like intrinsic dopants [31][32][33][34], molecules on the surface of monolayer MoS 2 [34][35][36][37][38], and carrier trapping at the interface between monolayer MoS 2 and the substrate [39]. The high sensitivity to the surrounding environment has led to the discovery of novel properties [31,[40][41][42]. Previous studies have demonstrated the enhancement or quenching of the PL intensity through defect engineering, adsorption of foreign molecules, thermal annealing, and structural disorder [32,43].…”
Section: Introductionmentioning
confidence: 99%